1979
DOI: 10.1111/j.1365-2265.1979.tb02101.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Somatostatin on Metabolic and Hormonal Changes During and After Exercise

Abstract: The effect of intravenous somatostatin on blood levels of metabolites and hormones has been examined in normal subjects who performed a 30-minute period of bicycle exercises at 70% maximal exercise capacity. The results have been compared with control studies in the same subjects. Measurements were made of blood levels of lactate, glucose, free fatty acids, glycerol, acetoacetate, 3-hydroxybutyrate, insulin, glucagon, growth hormone (hGH) and prolactin. Growth hormone and glucagon release were suppressed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The reduction in glucose concentration that occurred during exercise in the hormonal control groups was not attributable to a direct effect of somatostatin, since hypoglycemia does not develop during exercise in humans when somatostatin is infused without hormonal replacement (16). Also, when no exercise load was imposed on the subjects, normal values for glucose concentration and production were maintained for 4 h. Furthermore, Cherrington and associates (17) have demonstrated that there are minimal direct effects of somatostatin on the metabolism of glucose.…”
Section: Discussionmentioning
confidence: 94%
“…The reduction in glucose concentration that occurred during exercise in the hormonal control groups was not attributable to a direct effect of somatostatin, since hypoglycemia does not develop during exercise in humans when somatostatin is infused without hormonal replacement (16). Also, when no exercise load was imposed on the subjects, normal values for glucose concentration and production were maintained for 4 h. Furthermore, Cherrington and associates (17) have demonstrated that there are minimal direct effects of somatostatin on the metabolism of glucose.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that central a-1 and a-2 adrenergic stimulation during exercise leads to increased GHRH release, a response which can be abolished by the administration of somatostatin (17) or reduced by adrenergic antagonists such as phentolamine (18,19). Peripheral catecholamines, however, do not appear to influence GH release during exercise since there is a lack of any GH response to infused adrenaline (20).…”
Section: Discussionmentioning
confidence: 99%
“…Chalmers et al, under control conditions and during an octreotide infusion to suppress endogenous GH release, measured plasma metabolites including glucose, glycerol and free fatty acids during 30 min of exercise at 70% of VO 2max and 90 min of recovery [103]. No significant effect of GH Fig.…”
Section: Studies In Normal Subjectsmentioning
confidence: 97%